(3GdOdGFd (B( (3aj Yde CMcGe GdfLhe (B)s - (3CMeO Hf eMeO Hf YHO GdLdjd GdSLRj, CHh SYjO,J (B477 (3g` s
(3ChdgG (B:s
(3bGd (B: (3Efi deG fXQJ ai cJH GdChGFd ai UfGYI CMcGe GdfLhe , hacQJ ai YXje ebOGQgG CQOJ Cf CSJfHW cJGHkG jMJhi Ydi CUhdge s
(3BNQgG (B:s
(3GfUQGa GdbeQ Yf GdSYhO hCaYGdg HGdfMhS Odjd GdCNP HYO GdgQH , hcPdc EPG cGf UGMH GdWGdY hGdbeQ efMhSjf jOd Ydi Cfg jDNP , hGddg CYde Je GdOdGFd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3HgG JbWjYs
(3cJHJ Hbde ajg VHW eged GdfbW bdjdkGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs